PENCARIAN RUTE BERDASARKAN JARAK NODE TERDEKAT DAN EFISIENSI ENERGI PADA PROTOKOL ROUTING AOMDV DI JARINGAN MANET - Muhamad Rizqi Duha Pramudya; Andy Hidayat Jatmika; Raphael Bianco Huwae (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
The distance of nodes when communicating is a major challenge in route finding. The long distance of nodes will consume a lot of energy in the routing process so that the occurrence of failure or disconnection of the routing path becomes a problem that needs to be considered. One of the weaknesses in the AOMDV protocol is that it does not pay attention to node distance and node energy in the routing process. Therefore, this research proposes to modify the standard AOMDV routing protocol by adding the Preserving Energy Optimization Algorithm to identify node selection based on the node's distance to the source node by considering the node's energy in the routing process. The approach used includes modifications to the Hello message, so that the message has a geographic location based on x and y coordinates. The simulation was conducted using NS-2.35 on Linux Ubuntu operating system. The test parameters include energy consumption, end-to-end delay and packet delivery ratio (PDR). The simulation results of applying the PEO-AOMDV algorithm provide significant performance on all tested parameters. In terms of energy consumption, there is a saving of 16.04%. In addition, there is a decrease in average end-to-end delay by 43.08% to an increase in PDR percentage by 15.17% at various node density variations.